Financial Performance Evaluation of Manufacturing Companies Using Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) Methods (A Case Study of Manufacturing Companies Annual Reports on the IDX Website for the Years 2021–2024) - Dinda Oktaviantri; IGG Heru Marwanto; Nur Laely; Enni Sustiyatik (Journal of Innovative and Creativity, 2025)
This study aims to evaluate the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024 using financial ratios, namely Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER). The research employs a quantitative descriptive method with a documentation approach based on the companies’ financial statements. The sample consists of 33 manufacturing companies selected based on specific criteria. Secondary data were obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id).The results indicate that, in general, the financial performance of manufacturing companies during the period experienced fluctuations. ROA and ROE showed relatively stable trends, with several companies demonstrating excellent performance, such as Unilever Indonesia Tbk and Industri Jamu dan Farmasi Sido Muncul Tbk. Meanwhile, the DER ratio revealed variations in financial risk levels among companies, where some firms such as Krakatau Steel Tbk and Kimia Farma Tbk recorded very high DER values, reflecting a strong dependence on external financing. This study provides a comprehensive overview of the financial health of manufacturing companies in Indonesia and can serve as a reference for investors, management, and other stakeholders in making strategic decisions.